Contribution to the Forthcoming Modernisation in the Croatian Postal Traffic Technology - Bolarić, Marijan (Promet - Traffic&Transportation, 2012)
Postal administration world-wide is improving the postaltraffic also by introducing modem automation throughout itsoperation in mail transport.The Croatian Post must also carry out this demanding andchallenging project which must necessarily be well planned andimplemented as soon as possible. The automation of the operatingprocedures in the technological phases of mail-piecestransmission provides a significant substitution for the slowand expensive manual work, resulting in substantial reductionof costs, rise in the quality level of services and cutting down ofthe time-limit control of transmission.This is the aim of this article, as preliminary communication,which is based on the carried out research regarding importanttraffic parameters in the post centre Zagreb, as the largestone in Croatia. The results can also be used as adequate referencefonn for the research in other post centres ofCroatia. Afterthese studies and the obtained relevant infonnation, amethod of designing new rationally organised postal network ofCroatia in all segments of mail-pieces transmission would follow,as well as fanning of a suitable postal code and developingof the Croatian postal code map. This comprehensive workpresents the preparation phase of the project and it is absolutelynecessary for the success of the general automation in the Croatianpostal traffic.